Contributions of the Ethnographic Method in the Process of Linkage with the Community - Melendez, Hilarion Jose Vegas; Santana, Veronica Piedad Bravo; Rosillo, Diana Carolina Bravo; Macias, Eugenia Lyli Moreira (Journal of Posthumanism, 2025)
The main objective of the research is to categorize the contributions offered by the ethnographic method in the process of linking with the community; being complemented with the following specific objectives: 1. To identify the components of the ethnographic method that facilitate the approach with the community, and 2.- To interpret the perception of the participating researcher about the contributions of the ethnographic method in the process of linking with the community. The methodology applied is based on the phenomenological-hermeneutical paradigm, with a qualitative approach, whose method is descriptive and documentary, naturalistic and non-experimental, among the techniques of information collection are direct observation and focus group, having as key informants students of the last semester of the university degree in their practices of linking with the community. Among the main reflections is the fact that the ethnographic method adapts to different social groups and makes it possible to adjust approaches and techniques of data collection according to their particularities.